Initial oral microbiota and the impact of delivery mode and feeding practices in 0 to 2 month-old infants - Alejandra GARCÍA-QUINTANA; Annabella FRATTAROLI-PERICCHI; Sonia FELDMAN; Jesus LUENGO; Ana María ACEVEDO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this study was to describe the initial oral microbiota and how delivery mode and feeding practices impact its diversity in 0-2-month-old infants. This was a cross-sectional study that consisted of one collection of saliva samples from 0-2-month infants at baseline. Ten pairs of mothers and infants were selected. Medical health history, pregnancy, birth, feeding practices (breastfeeding or milk formula), and infant health status was obtained. Pooled microbial samples were obtained from the oral surfaces using a sterile cotton swab. Infants did not receive any breast milk before sampling. After collection, each swab was analyzed through microbiological culture-based procedures, using selective mediums. Cultures were analyzed for the presence of Streptococci, Lactobacillus, Staphylococcus, Enterobacterium , and Candida albicans . Twenty percent of the samples were serially diluted (10-2) to assess the number of bacteria expressed as CFU. Bacillota was the leading phylogenetic group in the infant's pooled microbial sample. The most prevalent genera were Streptococcus, Lactobacillus , and Staphylococcus . Two participants had a positive growth of Candida albicans . The association between genus group, type of delivery, and feeding practices was not statistically significant (p > 0.05). Lactobacillus genus was frequently present in the cesarean delivery group but with slightly higher counts in a vaginal delivery study subject. Exclusively breastfed infants showed presence of Streptococcus, Lactobacillus, Staphylococcus . The oral microbiome in infants (0-2 month-old) is highly heterogeneous and dynamic. Microbiota composition seems to be impacted by mode of delivery, with slight differences among groups. Breastmilk appears as an essential factor in maintaining the oral microbiome's stability and diversity.